Gastroprotective Effect of the Aqueous Fraction of Tamarindus indica L. Leaves Against Aspirin-Induced Gastric Injury in Mice - Sitti Rahimah; Maulita Indrisari; Devia Novelia Patabang (Jurnal Jamu Indonesia, 2026)
Tamarindus indica L. leaves contain bioactive compounds, particularly tannins and saponins, which may contribute to gastric mucosal protection. This study aimed to evaluate the gastroprotective effect of the aqueous fraction of T. indica leaves in aspirin-induced gastric injury in mice. Twelve mice were randomly divided into four groups (n = 3): normal control, negative control, and two treatment groups receiving the aqueous fraction at doses of 6 mg/30 g and 12 mg/30 g body weight prior to aspirin induction. Gastroprotective activity was assessed through macroscopic observation and histopathological examination of gastric tissues. Aspirin administration caused gastric mucosal injury characterized by erosion, ulceration, and hemorrhage. Treatment with the aqueous fraction reduced gastric damage and improved epithelial integrity. The dose of 12 mg/30 g body weight showed the most pronounced protective effect. These findings suggest that the aqueous fraction of T. indica leaves has potential gastroprotective activity.